Active head lifting from supine in infancy in the general population: Red flag or not?. (December 2021) - van Iersel, Patricia A.M.; Hadders-Algra, Mijna
Abstract: Background: Previously it had been had reported that active head lifting from supine (AHLS) in high-risk infants was associated with lower cognitive scores in the second year. AHLS was generally accompanied by stereotyped leg movements. Aims: To examine in a standardized way whether AHLS with or without stereotyped leg movements in the general population is associated with prenatal, perinatal, neonatal and socio-economic risk factors or with lower scores on concurrent infant tests. Study design: Cross-sectional study Subjects: 1700 infants aged 2–18 months representative of the Dutch population. Outcome measures: Infant Motor Profile (IMP) and Standardized Infant NeuroDevelopmental Assessment (SINDA). Assessments were video-recorded and included at the youngest ages 3min of behaviour in supine. AHLS and the presence of stereotyped leg movements were recorded. Standardized information on early risk factors was available. Results: AHLS occurred at 4–9 months (prevalence per months: 1–14%; highest prevalence at 6 months). It was not associated with early risk factors or scores on infant tests. When AHLS was accompanied by stereotyped leg movements it was associated with a higher prevalence of an IMP-variation score < P15 (Odds Ratio (OR) 2.472 [95%CI 1.017; 6.006]). Stereotyped leg movements irrespective of AHLS were associated with more unfavourable total IMP scores and IMP performance scores (B coefficients −3.212 [−4.065; −2.360], −2.521 [−3.783; −1.259]) and IMP variation and SINDA neurological scores (ORs 5.432 [3.409; 8.655], 3.098 [1.548; 6.202]). Conclusions: The data suggest that AHLS is not a red flag. Rather its co-occurring stereotyped leg movements may signal less favourable neurodevelopment. Highlights: Active head lifting from supine (AHLS) occurs at 4–9 months. AHLS occurs twice as often in girls than in boys. In the general population AHLS is not associated with early risk factors. AHLS is not associated with lower scores on concurrent infant tests. Stereotyped leg movements in infancy are associated with lower neuromotor scores.